TubeReport: Inovasi Media Pembelajaran Youtube dalam Menulis Teks Berita pada Siswa Kelas VIII SMPN 1 Galis Pamekasan - Desi Lusiana Fitriyah; Mochamad Arifin Alatas; Moh Hafid Effendy; Aldi Firnanda (Universitas Sebelas Maret, 2025)
Learning to write news texts is often perceived as difficult by students because the material presented is less related to real life. The purpose of this research is to describe the implementation of the TubeReport media innovation, the results of its use in news texts, and the students' responses in learning. This research uses descriptive qualitative methods. Data collection techniques were carried out through observation, interviews, and documentation. The research results show that the application of TubeReport media helps students in writing news texts that adhere to journalistic structure, from the application of the 5W+1H elements to the use of clear and informative language. Students responded positively through active participation in discussions, enhanced critical thinking skills, and greater interest in the world of journalism. In conclusion, TubeReport is an innovative learning medium that helps students write news texts by utilizing video broadcasts that are contextual, visual, and close to the realities of students' lives. Pembelajaran menulis teks berita kerap dirasakan sulit oleh siswa karena materi yang disampaikan kurang berkaitan dengan kehidupan nyata. Tujuan penelitian ini menggambarkan pelaksanaan inovasi media TubeReport, Hasil penggunaan dalam teks berita, dan respon siswa dalam pembelajaran. Penelitian ini menggunakan kualitatif deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan media TubeReport membantu siswa dalam menulis teks berita yang sesuai dengan struktur jurnalistik, mulai dari penerapan unsur 5W+1H hingga penggunaan bahasa yang lugas dan informatif. Siswa memberikan respon positif melalui partisipasi aktif dalam diskusi, kemampuan berpikir kritis yang lebih terasah, serta ketertarikan yang lebih besar terhadap dunia jurnalistik. Kesimpulannya, TubeReport adalah media pembelajaran inovatif yang membantu siswa dalam menulis teks berita dengan memanfaatkan tayangan video yang bersifat kontekstual, visual, dan dekat dengan realitas kehidupan siswa.